Hikmah Jadal dalam Al-Qur'an: Telaah Jadal dalam Proses Pengadilan - Luluk Indah kholifatin; Maslahatul Ummah; Abd Kholid (Journal of Islamic Education, 2025)
This article examines the concept of “jadal” in the Qur'an, which is a form of discussion or debate used as a means of communication and learning. The study is divided into several important parts. First, the theme of jaddal in the Qur'an is identified and analyzed, showing that jaddal is used to affirm the truth and guide humans towards a deeper understanding of Islamic teachings. Second, the purpose of jaddal is explained as a means of testing and strengthening faith, as well as encouraging humans to think critically and reflectively.Then, the article outlines the procedure of jaddal based on guidance from the Qur'an, which involves the use of rational arguments and thoughtful dialogue. The ethical evaluation of jadal according to the Qur'an emphasizes the importance of maintaining etiquette, honesty, and goodwill in any discussion. In this regard, jadal is seen as an activity that focuses not only on winning arguments, but also on discovering greater truths. The article also identifies the wisdom of jaddal in the Qur'an, namely as an educational tool that enriches religious understanding and strengthens social relations through constructive communication. Finally, the influence of jadal in Qur'anic interpretation is analyzed, showing that jadal can enrich interpretive perspectives and broaden religious understanding. With an analytical and critical approach, this article contributes to the academic literature by offering new insights into the role of jadal in theological and social dynamics in Islam, as well as its relevance in the context of modern society.